Tattoos : philosophy for everyone : I ink, therefore I am - Arp, Robert (Malden, MA : Wiley-Blackwell, 2012)
"Covering philosophical issues ranging from tattooed religious symbols to a feminist aesthetics of tattoo, Tattoos and Philosophy offers an enthusiastic analysis of inking that will lead readers to consider the nature of the tattooing arts in a new and profound way. Contains chapters written by philosophers (most all with tattoos themselves), tattoo artists, and tattoo enthusiasts that touch upon many areas in Western and Eastern philosophy Enlightens people to the nature of tattoos and the tattooing arts, leading readers to think deeply about tattoos in new ways Offers thoughtful and humorous insights that make philosophical ideas accessible to the non-philosopher"--
"Body art or eyesore, a celebration of individuality, or at very least a conversation piece, tattoos provide fertile ground for philosophical discussion, raising intriguing questions from aesthetics to feminism, from semiotics to the philosophy of the person. The abundance of tattooed religious symbols also raises questions surrounding the belief in and worship of God, and even the stigma associated with tattoos can initiate discussion on moral and political philosophy. Providing a broad arena for philosophical dialogue, essays include: Tattoos as an expression of freedom Confessions of a Tattooed Buddhist Philosopher Women and Tattoos Tattoos and personal identity Papers, enthusiastically inked by philosophers (most with tattoos), tattoo artists, and tattoo enthusiasts, offer enlightening insights into the nature of tattoos and the tattooing arts and the rich philosophical analysis that can be drawn from them"--
I ink, therefore, I foreword / Rocky Rakovic -- I am, therefore I ink : an introduction to tattoos : philosophy for everyone : I ink, therefore I am / Robert Arp -- Tattoos and the tattooing arts in perspective : an overview and some preliminary observations / Charles Taliaferro and Mark Odden -- How to read a tattoo, and other perilous quests / Juniper Ellis -- Are tattoos art? / Nicolas Michaud -- Fleshy canvas : the aesthetics of tattoos from Feminist and hermeneutical perspectives / Kimberly Baltzer-Jaray and Tanya Rodriguez -- Female tattoos and graffiti / Thorsten Botz-Bornstein -- Painted fetters : tattoooing as feminist liberation / Nancy Kang -- Tattoo you : personal identity in ink / Kyle Fruh and Emily Thomas -- Illusions of permanence : tattoos and the temporary self / Rachel C. Falkenstern -- My tattoo may be permanent, but my memory of it isn't / Clancy Smith -- Tattoos are forever : bodily freedom and the (im)possibility of change / Felipe Carvalho -- Bearing the marks : how tattoos reveal our embodied freedom / Jonathan Heaps -- Never merely 'there' : tattooing as a practice of writing and a telling of stories / Wendy Lynne Lee -- Something terribly flawed : philosophy and 'The illustrated man' / Kevin S. Decker -- The vice of the tough tattoo / Jennifer Baker -- To ink, or not to ink : tattoos and bioethics / Daniel Miori -- Writing on the body : the modern morality of the tattoo / Simon Woods -- Is a tattoo a sign of impiety? / Adam Barkman -- Confessions of a tattooed Buddhist philosopher / Joseph J. Lynch -- An atheist and a theist discuss a cross tattoo and God's existence / Robert Arp.
Includes bibliographical references and index.
Print version record.
Keywords: Tattooing; PHILOSOPHY; PHILOSOPHY -- General; ART -- Body Art & Tattooing; Tattooing; Electronic books